Targeting FGFR3 signaling and drug repurposing for the treatment of SLC26A2-related chondrodysplasia in mouse model - Li, Pan; Wang, Dong; Lu, Weiguang; He, Xin; Hu, Jingyan; Yun, Haitao; Zhao, Chengxiang; Yang, Liu; Jie, Qiang; Luo, Zhuojing (Journal of orthopaedic translation, 2024)
Mutations in Slc26a2 cause a spectrum of autosomal-recessive chondrodysplasia with a significant and negligible influence on the quality of life. It has been reported that Slc26a2 deficiency triggers the ATF6 branch of the UPR, which may, in turn, activate the negative regulator of the FGFR3 signaling pathway. However, the correlation between the deletion of Slc26a2 and the augmentation of downstream phosphorylation of FGFR3 has not been investigated in vivo. First, we constructed Slc26a2 and Fgfr3 double knockout mouse lines and observed gross views of the born mice and histological staining of the tibial growth plates. The second approach was to construct tamoxifen-inducible Cre-ERT2 mouse models to replicate SLC26A2-related non-lethal dysplastic conditions. Pharmacological intervention was performed by administering the FGFR3 inhibitor NVP-BGJ398. The effect of NVP-BGJ398 on chondrocytes was assessed by Alcian blue staining, proliferation, apoptosis, and chondrocyte-specific markers and then verified by western blotting for variations in the downstream markers of FGFR3. The growth process was detected using X-rays, micro-CT examination, histomorphometry staining of growth plates, and immunofluorescence. Genetic ablation of Fgfr3 in embryonic Slc26a2-deficient chondrocytes slightly attenuated chondrodysplasia. Subsequently, in the constructed mild dysplasia model, we found that postnatal intervention with Fgfr3 gene in Slc26a2-deficient chondrocytes partially alleviated chondrodysplasia. In chondrocyte assays, NVP-BGJ398 suppressed the defective phenotype of Slc26a2-deficient chondrocytes and restored the phosphorylation downstream of FGFR3 in a concentration-dependent manner. In addition, in vivo experiments showed significant alleviation of impaired chondrocyte differentiation, and micro-CT analysis showed a clear improvement in trabecular bone microarchitectural parameters. Our results suggested that inhibition of FGFR3 signaling pathway overactivation and NVP-BGJ398 has promising therapeutic implications for the development of SLC26A2-related skeletal diseases in humans. Our data provide genetic and pharmacological evidence that targeting FGFR3 signaling via NVP-BGJ398 could be a route for the treatment of SLC26A2-associated skeletal disorders, which promisingly advances translational applications and therapeutic development. SLC26A2 functions as a ubiquitously expressed sulfate transporter on the cell membrane, enabling intracellular delivery of inorganic sulfate. Mutations in Slc26a2 result in a spectrum of autosomal recessive chondrodysplasia. Overactivation of FGFR3 signaling may be an underlying contributor to the pathogenicity of SLC26A2 deficiency. By constructing genotypic and induced developmental Slc26a2 deletion mutant mice, over-activation of the phosphorylation signaling pathway downstream of FGFR3 (p-ERK1/2 and p-STAT1) in chondrocytes caused by Slc26a2 deletion could be effectively inhibited by targeting the FGFR3 route, and inhibition of FGFR3 from genetic or pharmacological inhibitor NVP-BGJ398 intervention could improve chondrogenesis in Slc26a2 knockout mice by regulating chondrocyte survival, proliferation, and differentiation, and significantly ameliorate the abnormal skeletal development phenotype. [Display omitted]